2010
DOI: 10.1053/j.gastro.2010.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Medications (NSAIDs, Statins, Proton Pump Inhibitors) and the Risk of Esophageal Adenocarcinoma in Patients With Barrett's Esophagus

Abstract: Background & Aims Limited evidence suggests that proton pump inhibitors (PPI), non-steroidal anti inflammatory drugs (NSAID)/aspirin and statins may be associated with low risk of esophageal neoplasia. However, the possible effect these medications may have on the risk of esophageal adenocarcinoma (EAC) in patients with existing Barrett’s esophagus (BE) is unclear. Methods We conducted a nested case-control study in a cohort of patients with BE identified in the national Department of Veterans Affairs (VA) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
181
1
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(188 citation statements)
references
References 21 publications
4
181
1
2
Order By: Relevance
“…Several individual studies (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)27) and 2 systematic reviews (that produced essentially identical results despite slightly different methodologies (16,17)) have reported that statin use, and particularly statin use combined with a cyclo-oxygenase inhibitor, is associated with a reduced incidence of esophageal adenocarcinoma. This has been reported in cohort studies and case-control studies of Barrett's patients and population-based studies compared to population-based controls, although not all studies are in agreement (28).…”
Section: Discussionmentioning
confidence: 99%
“…Several individual studies (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)27) and 2 systematic reviews (that produced essentially identical results despite slightly different methodologies (16,17)) have reported that statin use, and particularly statin use combined with a cyclo-oxygenase inhibitor, is associated with a reduced incidence of esophageal adenocarcinoma. This has been reported in cohort studies and case-control studies of Barrett's patients and population-based studies compared to population-based controls, although not all studies are in agreement (28).…”
Section: Discussionmentioning
confidence: 99%
“…A study from Australia showed that patients who took aspirin at least weekly had significantly lower risks of [142]. In a nested case-control study of individuals with BE, an inverse association was found between filled NSAID/ aspirin prescriptions and EAC, which remained significant when adjusted for PPI prescription, among other factors (incidence density ratio 0.64, 95 % CI 0.42-0.97) [132]. Similarly, a recent meta-analysis demonstrated that compared to nonusers, individuals who have used aspirin or nonaspirin NSAIDs had a significantly reduced risk of EAC.…”
Section: Neoplastic Preventionmentioning
confidence: 97%
“…Epidemiological studies have shown that the long-term use of PPIs is associated with lower rates of dysplasia and EAC in patients with BE [122,124,[129][130][131], except for one study [132]. In two other studies, the early use of a PPIs after the diagnosis of BE was associated with a decreased risk of developing dysplasia or EAC [122,129] ( Table 4).…”
Section: Neoplastic Preventionmentioning
confidence: 99%
“…Since 2003, several observational studies comparing BE and EAC patients have been published (Table 1). These were either case-control retrospective [23,37,38] or cohort studies [39][40][41][42][43] . Prospective chemoprevention trials are underway to evaluate the efficacy of aspirin and NSAIDs.…”
Section: Nsaids and Eac Chemopreventionmentioning
confidence: 99%
“…Kantor et al [43] reported that non-aspirin NSAID use reduced the risk of neoplastic progression but not aspirin use. The other 3 cohort studies were negative [41][42][43] , although Kantor found that NSAID use was beneficial only for patients with high-grade dysplasia. A pooled analysis of 6 population-based studies within the Barrett's and Esophageal Adenocarcinoma Consortium have shown that daily NSAID use can reduce the risk of developing EAC by more than 40% (OR = 0.56, 95%CI: 0.43-0.73, P < 0.001) [47] .…”
Section: Nsaids and Eac Chemopreventionmentioning
confidence: 99%